Ecological opportunity and the onset of polyploid niche expansion waves - Felipe Kauai; Yves Van de Peer; Dries Bonte (Proceedings of the National Academy of Sciences, 2026)
Polyploidy, the presence of more than two sets of chromosomes, has evolved many times across the tree of life, yet we still do not know why some polyploid lineages persist while most go extinct. The establishment of polyploid populations is often reported to be associated with harsh environmental conditions, and stress tolerance in particular, which has led to the widespread view that polyploidy-specific niche requirements are key to their persistence at ecological and evolutionary timescales. Here, we reevaluate this perspective using a classical mathematical model of polyploid establishment, presenting analytical and numerical results, along with an empirical case study. We show that simple eco-evolutionary processes at the margins of diploid range-expansion waves, more specifically ecological drift and dispersal limitation, can be sufficient to allow polyploid populations to carve out their own space, without any a priori adaptive advantage over their diploid ancestors. Our modeling effort reveals three key insights. First, polyploids most readily gain a foothold at the low-density front of a diploid range expansion wave, where ecological drift is strongest. Second, limited dispersal accelerates spatial clustering of polyploid organisms through assortative mating. Third, once spatially segregated along gradients, diploid and polyploid populations are expected to experience distinct environments, allowing natural selection to drive niche divergence. We illustrate these interconnected principles by simulating the phylogeographic history of a well-documented autopolyploid complex of Neobatrachus, Australian burrowing frogs. Altogether, our results provide a neutral baseline against which the ecological consequences of polyploidization can be more easily inferred within natural populations.